“COMPARISON OF ULTRASOUND AND CHEST X-RAY FOR LOCALIZATION OF CENTRAL VENOUS CATHETER - NAWADAT, Q; KHALID, MA; ATTA, A (Biological and Clinical Sciences Research Journal, 2023)
We are pleased to inform you that your manuscript No. MS/BCSRJ/2023/2200311305, Titled: “COMPARISON OF ULTRASOUND AND CHEST X-RAY FOR LOCALIZATION OF CENTRAL VENOUS CATHETER,” received on 9 th September 2022 and under consideration with BCSRJ has been approved by reviewers and our editorial team on 21st May 2023 for publication in the Volume 2023 of “Biological and Clinical Sciences Research Journal (BCSRJ).”